Review of external ocular compression: clinical applications of the ocular pressure estimator - Korenfeld MS (Dove Medical Press, 2016)
Michael S Korenfeld,1,2 David K Dueker3 1Comprehensive Eye Care, Ltd. Washington, MO, USA; 2Washington University Department of Ophthalmology and Visual Sciences, St Louis, MO, USA; 3Ophthalmology, Hamad Medical Corporation, Doha, Qatar Purpose: The authors have previously validated an Ocular Pressure Estimator (OPE) that can estimate the intraocular pressure (IOP) during external ocular compression (EOC). The authors now apply the OPE in clinical states where EOC is clinically important. The original work is described for two periods of risk: during sleep and during the digital ocular massage (DOM) maneuver used by surgeons after trabeculectomy to keep the operation functional. Other periods of risk for external ocular compression are then reviewed.Methods: The first protocol estimated the IOP in the dependent eye during simulated sleep. Subjects had their IOPs initially measured in an upright-seated position, immediately upon assuming a right eye dependent side sleeping position (with nothing contacting the eye), and then 5 minutes later while still in this position. While maintaining this position, the fluid filled bladder of the OPE was then placed between the subject’s closed eye and a pillow during simulated sleep. The IOP was continuously estimated in this position for 5 minutes. The subjects then had the IOP measured in both eyes in an upright-seated position. The second protocol determined if a larger vertical cup-to-disc ratio was more common on the side that patients reported they preferred to sleep on. The hypothesis was that chronic asymmetric, compression induced, elevations of IOP during sleep would be associated with otherwise unexplained asymmetry of the vertical cup-to-disc ratio. The third protocol assessed the IOP during DOM. The OPE was used to characterize the IOP produced during the DOM maneuver of five glaucoma surgeons. After this, 90 mmHg was chosen as a target pressure for DOM. The surgeons were then verbally coached during three additional compressions. After a 5-minute period, the surgeons were asked to reproduce this targeted IOP during subsequent compressions.Results: The mean IOP during the “sleep session” was 22±5 mmHg (SEM). The mean peak pressure was 40±11 mmHg (SEM) and the mean trough pressure was 15±2 mmHg (SEM). There was a 78% agreement between the eye that was reported to be dependent during sleep and the eye with the larger vertical cup-to-disc ratio, for eyes with at least a 0.10 cup-to-disc ratio difference, P=0.001, n=137. The OPE estimated an average induced IOP during typical DOM of 104±8 mmHg (SEM), with each compression having an average range of 17±3 mmHg (SEM). After coaching, and a 5-minute waiting period, the average induced IOP reduced to 95±3 mmHg (SEM) with a reduced average range of IOP to 11±1 mmHg.Conclusion: The OPE was successfully used to estimate the IOP while subjects experienced EOC during normal sleep postures. These EOC-induced elevations of IOP were considerable, and likely contribute to significant ocular pathology, not only for glaucoma, but for retinal vascular occlusive diseases, retinal vascular leakage, and the induction of the ocular-cardiac reflex in infants, as well. The correlation of a larger vertical cup-to-disc ratio in patients with a sleep posture preference suggests a causal relationship, since patients with other conditions known to be associated with cup-to disc ratio asymmetry were excluded from this study. The OPE is a useful device to teach DOM to surgeons and patients for home use. Keywords: sleep posture, intraocular pressure, nocturnal, cup-to-disc ratio asymmetry, glaucoma, digital ocular massage